Gender and racial differences in nonalcoholic fatty liver disease - Pan, Jen-Jung (World journal of hepatology, 2014)
Due to the worldwide epidemic of obesity, nonalcoholic fatty liver disease(NAFLD) has become the most com-mon cause of elevated liver enzymes. NAFLD represents a spectrum of liver injury ranging from simple steato-sis to nonalcoholic steatohepatitis(NASH) which may progress to advanced fibrosis and cirrhosis. Individuals with NAFLD, especially those with metabolic syndrome, have higher overall mortality, cardiovascular mortality, and liver-related mortality compared with the general population. According to the population-based studies, NAFLD and NASH are more prevalent in males and in Hispanics. Both the gender and racial ethnic differences in NAFLD and NASH are likely attributed to interaction between environmental, behavioral, and genetic fac-tors. Using genome-wide association studies, several genetic variants have been identified to be associated with NAFLD/NASH. However, these variants account for only a small amount of variation in hepatic steatosis among ethnic groups and may serve as modifiers of the natural history of NAFLD. Alternatively, these variants may not be the causative variants but simply markers representing a larger body of genetic variations. In this article, we provide a concise review of the gender and racial differences in the prevalence of NAFLD and NASHin adults. We also discuss the possible mechanisms for these disparities.